ANALISIS PEMASARAN IKAN PATIN SIAM (Pangasius hypophtalmus) PADA KELOMPOK USAHA BERSAMA KARYA KELUARGA DI KELURAHAN SUNGAI KAPIH KOTA SAMARINDA - Alif Firdaus; Muhammad Syafril; Wahyu Fahrizal (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
The study aimed to determine marketing channels, margins, marketing profits, farmer's share, and marketing functions of Siamese catfish (Pangasius hypophtalmus) in Sungai Kapih Village, Samarinda City. The research was carried out from October 2021 to August 2022 at the Karya Keluarga Joint Business Group in Sungai Kapih Village, Samarinda City. The samples used in this study were 10 fishermen members of the Karya Keluarga Joint Business Group and 2 Siamese catfish middlemen. The sampling method used purposive sampling, census, and snowball sampling. The results showed that the marketing channel of siamese catfish formed in Sungai Kapih Village only consisted of one marketing channel pattern, namely the second level marketing channel (2) consisting of fishermen, local collector, and retailer. The total marketing margin obtained is Rp. 15,000/kg. The total marketing profit obtained is Rp. 12,910.87/kg. The farmer's share value obtained is 70% classified as efficient marketing. The marketing functions carried out by each marketing agency are the exchange function, the physical function, and the facility function.